DNA Three‐Way Junction for Differentiation of Single‐Nucleotide Polymorphisms with Fluorescent Copper Nanoparticles. Issue 29 (24th April 2017) - Sun, Feifei; You, Ying; Liu, Jie; Song, Quanwei; Shen, Xiaotong; Na, Na; Ouyang, Jin
Abstract: A label‐ and enzyme‐free fluorescent sensor for the detection of single‐nucleotide polymorphisms (SNPs) at room temperature is proposed, using new copper nanoparticles (CuNPs) as fluorescent reporters. The CuNPs were constructed by using a DNA three‐way junction (3WJ) template. In this assay, two complementary adenine/thymine‐rich probes can hybridize with the wild‐type target simultaneously to construct a 3WJ structure, serving as an efficient scaffold for the generation of CuNPs. However, the CuNPs produce weak fluorescence when the probes bind with a mutant‐type target. SNPs can be identified by the difference in fluorescence intensity of the CuNPs. This SNPs detection strategy is straightforward, cost‐effective, and avoids the complicated procedures of labeling or enzymatic reactions. The fluorescent sensor is versatile and can be applied to all types of mutation because the probes are programmable. Moreover, the sensor exhibits good detection performance in biological samples. Abstract : Fluorescent copper nanoparticles (CuNPs) are applied for single‐nucleotide polymorphisms (SNPs) detection. Two probes combine with a target DNA simultaneously, and when the target is fully matched with the probes, a DNA three‐way junction (3WJ) is formed, which can act as a good template for the CuNPs. However, a mutant base in the target can hinder the creation of the 3WJ, so that the CuNPs generation fails. The SNPs differentiation can be achieved by the fluorescence intensity.